Experimental validation of tangential resolution improvement in photoacoustic tomography using modified delay-and-sum reconstruction algorithm - Kalva, Sandeep Kumar (2016)
For a circular scanning geometry in photoacoustic tomography, the axial/radial resolution is spatially invariant and is not affected by the ultrasound transducer (UST, detector) aperture. However, the tangential resolution is dependent on the detector aperture size and it varies spatially. Many techniques were proposed to improve the tangential resolution, such as attaching a concave lens in front of the nonfocused transducer or using a virtual point detector. Both of these methods have difficulties. Therefore, a modified delay-and-sum reconstruction algorithm has been proposed which can be used together with a standard ultrasound detector (nonfocused) to improve the tangential resolution. In this work, we validate the modified delay-and-sum algorithm experimentally for both flat and cylindrically focused USTs. More than threefold improvement in tangential resolution is observed. It is also shown that the object shape is recovered with this modified algorithm, which is very helpful for diagnosis and treatment purposes.